PERAN MOTIVASI SEBAGAI MEDIASI TERHADAP HUBUNGAN PENGAWASAN DAN KINERJA KARYAWAN (Studi Kasus Pada PT. Asuransi Central Asia Cab. Jambi) - Ubaidillah Ubaidillah (Universitas Batanghari Jambi, 2018)
This study aims to look at the effect of supervision on employee performance at PT.Asuransi Central Asia, Tbk Jambi Branch, and the role of motivation as a mediating variable on the relationship between supervision and performance. The data in this study uses qualitative data by distributing questionnaires that include alternative answers that have been provided to respondents. After the data is collected, it is then analyzed to answer the formulation of the problem using the path analysis method. The results of this study indicate that supervision influences employee performance either directly or through motivation as a mediating variable.